Water Governance in Bangladesh: An Evaluation of Institutional and Political Context - Ngai, Weng Chan; Roy, Ranjan; Brian C., Chaffin (MDPI, 2016)
Water crises are often crises of governance. To address interrelated issues of securing access to sustainable sources of safe water for the world’s populations, scholar and practitioners have suggested fostering improved modes of water governance that support the implementation of integrated water resource management (IWRM). Recently, implementation of an IWRM approach was announced as a target for achieving Goal 6 of the Sustainable Development Goals (SDGs). This study employs an analytical hierarchy process with a SWOT analysis to assess the current institutional and political context of water governance in Bangladesh and evaluate IWRM as a means to achieve the SDGs.